Comparison of the effectiveness and safety of formoterol versus salmeterol in the treatment of patients with asthma: A systematic review and meta-analysis - Ashraf Velayati; Seyed Alireza Hosseini; Ali Akbari Sari; Farideh Mohtasham; Mostafa Ghanei; Mohsen Yaghoubi; Reza Majdzadeh (Journal of Research in Medical Sciences, 2015)
Background: Formoterol and salmeterol are two long-acting β2-agonists given by inhalation, with bronchodilating effects lasting for at least 12 h after a single administration. Formoterol has a faster onset of action compared with salmeterol. The aim of this study was to perform a systematic review and meta-analysis on the data published from previous review in order to calculate pooled estimates of effectiveness and safety assessment of formoterol and salmeterol in treatment of patients with asthma. Materials and Methods: In this study, we conducted an electronic search for medical citation databases including Cochrane, PubMed, Scopus, PsycInfo, and IranMedex. Besides manual search of the databases that record randomized clinical trials, conference proceedings, and journals related to asthma were included. Studies were evaluated by two independent people based on inclusion and exclusion criteria, and the common outcomes of studies were entered into the RevMan 5.0.1 software, after evaluation of studies and extraction of data from them; and in cases where there were homogeneous studies, meta-analysis was performed, and for heterogeneous studies, the results were reported qualitatively. Results: Of the 1539 studies initially found, 13 were included in the study. According to the meta-analysis conducted, no significant difference was found between the inhalation of formoterol 12 μg and salmeterol 50 μg in the two outcomes of mean forced expiratory volume 1 s (FEV1), 12 h after inhalation of medication and Borg score (A frequently used scale for quantifying breathlessness) after inhalation of medication. In addition, salmeterol was more effective than formoterol in the two outcomes of percent decrease in FEV1 after inhalation of methacholine and the number of days without an attack. Since the two outcomes of FEV1 30-60 min after inhalation of medication and morning peak expiratory flow after inhalation of medication were heterogeneous, they had no meta-analysis capabilities, and its results were reported qualitatively. Conclusion: The data from included studies shows that, more efficacy has been achieved with Salmeterol, especially in some outcomes such as the percent decrease in FEV1 after inhalation of Methacholine, and the number of days without an attack; and therefore, the administration of Salmeterol seems to be beneficial for patients, compared with Formoterol.